The idea of Context and Contextual Qur’anic Interpretation - Dr. Shahzadi Pakeeza,; Mariam Bushra, (Al-Qanṭara, 2022)
In the domain of Qur’ānic interpretation, there has been significantly less emphasis on contextualization in contrast to literalism and textualism concerning both classical and modern periods. Given the differences between the contexts of the time of Qur’ānic revelation and those of the modern world (i.e., social, economic, cultural contexts etc.), several Muslim scholars have recognized the need of reinterpretation of specific Qur’ānic texts throughout the modern period. Towards this ,the main focus of this library-based research is to explore the contextual interpretation of the holy Qur’ān to study how this approach can enable the Muslims of the contemporary era to follow its ethical teachings according to their contexts. The research shows that the contextual approach to Qurʼānic interpretation aims at understanding the real implication of Qurʼānic message by contextualizing certain ideas and concepts of the holy Qurʼān. The contextual approach to Qurʼānic interpretation does not modify the fundamental Qurʼānic values, beliefs or practices but it makes a room for the interpreter to consider the changing situations and contexts.